The Vividness of Motor Imagery Is Correlated With Corticospinal Excitability During Combined Motor Imagery and Action Observation - Moriuchi, Takefumi; Nakashima, Akira; Nakamura, Jiro; Anan, Kimika; Nishi, Keita; Matsuo, Takashi; Hasegawa, Takashi; Mitsunaga, Wataru; Iso, Naoki; Higashi, Toshio (Frontiers in Human Neuroscience, 2020)
The present study aimed to investigate the relationship between motor imagery (MI) assessment (ability and quality) and neurophysiological assessment (transcranial magnetic stimulation (TMS)-induced motor-evoked potentials (MEP)) during MI. Sixteen subjects completed an MI task playing the piano with both hands, and neurophysiological assessment was performed during the MI task. The Motor Imagery Questionnaire-Revised was adopted to evaluate MI ability, while the Visual Analogue Scale (VAS) was adopted to evaluate MI quality. A TMS pulse was delivered during the MI task, and MEPs were subsequently recorded in the abductor pollicis brevis. We found a significant positive correlation between the VAS score and the TMS-induced MEPs (ρ = 0.497, p < 0.001). These findings suggest that the MI VAS score could potentially reflect the excitability of the primary motor cortex during MI, particularly in complex MI tasks.